TINJAUAN TATA KELOLA RUANG FILLING BERDASARKAN ILMU ERGONOMI DI PUSKESMAS WANAREJA 1 - Ayu Amelia (Jurnal Infokes, 2023)
The lighting for the medical record room at the Wanareja Health Center 1 was uneven throughout the room and the area of ​​the storage room did not meet the standards. This type of research is descriptive qualitative. The object used is the medical record room. The research instruments were room thermometer, meter and lux meter. How to collect data by observation and interviews. For data analysis using descriptive analysis. The results of the study showed that the lighting in the medical record document storage room at the Wanareja Health Center 1 ranged from 137-140 lux but was not evenly distributed throughout the room while the patient registration room ranged from 101-103 lux, the temperature of the medical record room was 23.1oC, the humidity in the medical record room that is 51% so that includes humidity, storage space area of ​​4 m² x 2.5 m² x 3 m². This affects the productivity and performance of the officers themselves. Based on the research results, the proposed solutions and suggestions are expected to improve the lighting of the medical record room and increase the area of ​​the room to make it easier for officers to retrieve or return medical record files so that they comply with established standards and it is advisable to provide lighting, temperature and humidity measuring devices. Keywords: Ergonomics Aspect, Layout, Medical Record Storage.